The Clinical Outcomes of Ventricular Septal Rupture Secondary to Acute Myocardial Infarction: A Retrospective, Observational Trial - Xin-Ying Zhang; Li-Zhao Bian; Nai-Liang Tian (Journal of Interventional Cardiology)
Background. Ventricular septal rupture (VSR) is a severe mechanical complication secondary to acute myocardial infarction (AMI) with a dreadful prognosis. The goal of our study was to evaluate the mortality and to identify the predictors of mortality for this population. Methods. From June 2012 to July 2021, patients with VSR secondary to AMI were initially screened for eligibility in this study. The potential risk predictors were determined using appropriate logistic regression models. Results. In this retrospective study, a total of 50 cases were included, and 14 patients survived and got discharged successfully. Univariable analyses indicated that the heart rate (HR), white blood cell (WBC) count, neutrophils count, serum glucose, serum creatinine, serum lactic acid, and the closure of rupture were significantly associated with mortality among these special populations. Conclusion. This study found that such high mortality in patients with VSR after AMI was significantly correlated with these risk factors representing sympathetic excitation and large infarct size. Coronary revascularization combined with the closure of rupture might be helpful in improving their prognosis.